Hubungan Aktivitas Fisik dan Tingkat Stress dengan Derajat Hipertensi pada Lansia di Posyandu Lansia Jalakan Hargosari - Putri Silvia Dewi; Norman Wijaya Gati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The aging process in the elderly will result in changes the cardiovascular organs, which will cause various diseases such as hypertension. Hypertension is still a problem found in Indonesian society. According to the Ministry of Health, in 2020 more than 427,218 people died due to hypertension. If it is not controlled, it will reduce life expectancy in the elderly. To determine the relationship between physical activity and stress levels with the degree of hypertension in the elderly at the Jalakan Hargosari Elderly Posyandu. This research uses analytic quantitative research with a cross sectional approach. Sampling using purposive sampling. The number of samples is 49 respondents. The instruments used PSS and PASE used the Spearman rank test. The results of this study using the Spearman rank obtained a p value (Physical activity 0.014) and a p value (Stress level 0.003) which showed a p-value <0.05 meaning Ha1 and Ha2 were accepted. There is a relationship between physical activity and stress levels with the degree of hypertension in the elderly at the Posyandu for the elderly in Hargosari.